A standardised protocol for measuring farmland biodiversity outcomes across European Farmer Cluster landscapes - Rachel N. Nichols; Graham S. Begg; Lisette Cantú-Salazar; John M. Holland; Youri Martin; John Tzilivakis; Sarah Vray; Douglas J. Warner; Alon Zuta; Niamh M. McHugh (PLoS ONE, 2026)
Farmland biodiversity has declined, with agricultural intensification cited as a major contributing factor. Therefore, monitoring farmland biodiversity in a consistent manner is a crucial aspect of determining if conservation efforts are aiding in its recovery. “Farmer Clusters” comprise groups of neighbouring farmers who have identified and instigated their own biodiversity targets as a collective. These provide an opportunity to assess the impact of collaborative conservation efforts on farmland biodiversity at the landscape-scale. Through the FRAMEwork project (Farmer clusters for Realising Agrobiodiversity Management across Ecosystem), an EU Horizon 2020 project, eleven Farmer Clusters were established across Europe, and their biodiversity monitored in a Before-After-Control-Impact (BACI) experiment. The aim of this paper is to describe and critically evaluate the methods applied to monitor biodiversity across these landscapes. Once relevant landscape-scale biodiversity indicators were identified, the protocol was assembled. Guidance to select appropriate survey squares and transects in different farming systems and European landscapes that are representative of the different farmland habitats are provided. The monitoring protocol also describes how to conduct biodiversity surveys of birds, pollinators (bumblebees, butterflies, solitary bees, and hoverflies), and vegetation within these survey squares. The methods comprise of a combination of well-documented procedures, presented as a single, standardised protocol that can be replicated in different farming systems and landscapes throughout Europe. Anticipated results are also presented, demonstrating how the methods might contribute towards the BACI analysis, as well as multi-taxa, community-level biodiversity analysis. Finally, an evaluation of the biodiversity indicators and survey methods used is also given. Through FRAMEwork, these methods will be used to assess the effectiveness of Farmer Clusters at improving landscape-scale biodiversity.